2013
DOI: 10.1177/001440291307900203
|View full text |Cite
|
Sign up to set email alerts
|

Moving Research into Practice: Can We Make Dissemination Stick?

Abstract: I n his 1993 Academy of Management Presidential address, Hambrick (1994) opined that academics seem to have a minimalist ethos: . . . minimal innovation, minimal visibility, minimal impact. Each August, we come to talk to each other [at the Academy of Management's annual meeting]; during the rest of the year we read each others' papers in our journals and write our own papers so that we may, in turn, have an audience the following August: an incestuous, closed loop. Colleagues, if we believe highly in what we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 76 publications
0
53
0
2
Order By: Relevance
“…Os desafios atuais implicam uma aliança entre diferentes atores, das autoridades educativas, às universidades e escolas, no sentido de aprofundar esta cultura inclusiva. Parece necessária a criação de oportunidades de formação específica neste domínio, aprofundando a relação entre os desenvolvimentos teóricos e da investigação, com as práticas dos educadores no seu trabalho quotidiano (DUCHNOWSKI et al, 2006;COOK;COOK;LANDRUM, 2013). Importa, portanto, promover nos programas de formação um maior contacto com a literatura de referência, permitindo compreender melhor a investigação, explorar a sua importância e ajudar a perceber como aplicar os …”
Section: Discussão E Conclusõesunclassified
“…Os desafios atuais implicam uma aliança entre diferentes atores, das autoridades educativas, às universidades e escolas, no sentido de aprofundar esta cultura inclusiva. Parece necessária a criação de oportunidades de formação específica neste domínio, aprofundando a relação entre os desenvolvimentos teóricos e da investigação, com as práticas dos educadores no seu trabalho quotidiano (DUCHNOWSKI et al, 2006;COOK;COOK;LANDRUM, 2013). Importa, portanto, promover nos programas de formação um maior contacto com a literatura de referência, permitindo compreender melhor a investigação, explorar a sua importância e ajudar a perceber como aplicar os …”
Section: Discussão E Conclusõesunclassified
“…the research-to-practice gap, such as calling for better dissemination of research results to better effect changes in the classroom (e.g., Cook, Cook, & Landrum, 2013;Ducharme & Shecter, 2011;Grima-Farrell et al, 2011). They have suggested examining other fields that effectively use new developments in knowledge to transform practice, such as marketing theory (Cook et al, 2013), medicine, design, and consumer electronics engineering (Burkhardt & Schoenfeld, 2003).…”
Section: Teacher Behavior Change Researchers Have Made Various Propomentioning
confidence: 99%
“…They have suggested examining other fields that effectively use new developments in knowledge to transform practice, such as marketing theory (Cook et al, 2013), medicine, design, and consumer electronics engineering (Burkhardt & Schoenfeld, 2003). Others have suggested that researchers and practitioners should collaborate more closely to design and implement professional development to better meet the needs of teachers (Gore & Gitlin, 2004;Korthagen, 2007).…”
Section: Teacher Behavior Change Researchers Have Made Various Propomentioning
confidence: 99%
See 2 more Smart Citations